Efficacy and Safety of Empagliflozin as Add-On Therapy in Patients of Type-2 Diabetes Mellitus - Nauman Wazir; Shafqat Ur Rehman (Gandhara University, 2022)
OBJECTIVES: To assess efficacy of two doses i.e., 10 mg and 25 mg in lowering the glycated haemoglobin (HbA1C) and fasting blood glucose (FBG) in patients of type 2 diabetes mellitus (T2DM) having suboptimal glycaemic control on maximal doses of Metformin and Sitagliptin, and to see the frequency of its side-effects. METHODOLOGY: The study design was a randomized control trial. Fifty nine adult patients of T2DM who were already on 2000 mg of Metformin and 100 mg of Sitagliptin and were having suboptimal glycaemic control (HBA1C >7% and <12%) were randomized to two groups, one group receiving 10 mg (Group A) and the other group receiving 25 mg of empagliflozin (Group B) as an additional treatment. HbA1C and FBG were taken before and 12 weeks after addition of empagliflozin in both the groups. Side effects of empagliflozin such as urinary tract infections (UTI) and genital mycotic infections were also recorded in both the groups. RESULTS: Total patients in-group A were 31 and their mean age was 51.48±4.29 years. In-group B there were 28 patients and their mean age was 52.39±5.20 years. There was a statistically significant reduction of both HbA1C and FBG in both the groups after empagliflozin treatment; (p=0.000) for both HbA1C and FBG in both the groups. Although numerically UTI and genital mycotic infections were more than pre-treatment numbers, they were not statistically significant (p>0.05). CONCLUSION: Empagliflozin can be safely added to the oral anti-diabetic regimen of patients with type 2 diabetes mellitus who have suboptimal glycaemic control and results in significant improvement in HbA1C.